Mutagenesis and functional studies of the HIV-1 vpr gene and Vpr protein obtained from South African virus strains - Romani, Bizhan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD)--University of Stellenbosch, 2011.